[DETERMINATION ON MATURITY LEVEL OF SALAM (Syzygium polyanthum (WIGHT) WALPERS) FRUIT FOR SEEDLING USING GERMINATION TEST AND SEED VIGOR] - Ninik Setyowati; Ahmad Fadli (Pusbindiklat - LIPI, 2015)
Study on the determination of the maturity level of salam (Syzygium polyanthum (Wight) Walpers) fruit for seedling with germination test and vigor of seed was conducted at Macropropagation Laboratory, Research Centre for Biology, Cibinong Science Center. The experiments were carried out in 3 stages i.e. stage-1, observation of morphological and anatomical characteristics of fruits and seeds. Stage-2, determine of seed germination percentage on 3 levels of fruit maturity. Stage-3, determine of seedling vigor in 3 level of fruit maturity. There were arranged with a Completely Randomized Design. The results showed that there were 3 levels of fruit maturity of Syzygium polyanthum based on morphological of skin color i.e. pre-ripe (reddish green), ripe (red) and after-ripe (red-black). In general, the morphological characteristics of fruits and seeds of ‘salam’ was not different i.e. the fruit is globular buni, slick texture; and the seeds is oval, soft texture, the location of ‘hilum’ at the end, elongated shape, the color is white, position concave. The color of the endosperm is green, the embryo located at the base, and the color is green. However, different in size, the more mature fruit, the larger diameter (8.0-13.7) mm, thick meat (1.0-2.4) mm, as well as the diameter of seed, either cross-sectional (3,2-8.0) mm and longitudinal (3.9-10.1) mm. The seeds germinate quickly, on day 2 already germinated 10-20%, on day 7 reaches 80-95%. The percentage of seed germination at pre-ripe fruit showed the highest (93.33%), the highest germination rate, the most rapid germination rate (3.83 days), also the highest germination value (226.67) than the other. There for, it was recommended for the harvesting of fruit on the pre-mature level, with the color fruit of reddish green.